Daily Worship Program And Qur’an Recitation In The Formation Of Islamic Character At MAN 1, Gorontalo Regency - Nola Novita Buhohang; Burhanudin Ak Mantau; Muhammad Zainul Arifin; Saifullah; Arya Pradana; Alfadhli; Ni'ma M. Alhabsyi (Academicus: Journal of Teaching and Learning, 2026)
This study aims to describe the implementation of the daily worship program and Qur’anic tadabbur, as well as the supporting and inhibiting factors in forming students’ Islamic character at MAN 1 Gorontalo Regency. The research used a descriptive qualitative approach with data collected through observation, interviews, and documentation involving the head of the madrasah, Islamic Religious Education teachers, tahfidz supervisors, and students. The data were analyzed through data condensation, data display, and conclusion drawing, while data validity was strengthened through source and technique triangulation. The findings show that the daily worship program is implemented through congregational dhuha prayer, Qur’an recitation before learning, congregational dzuhur prayer, sunnah prayer, short sermons, and routine evaluation. Qur’anic tadabbur is carried out through talaqqi, interactive discussion, contextualization of verses, and guided reflection so that students do not merely read or memorize the Qur’an, but also understand and practice its values. The program strengthens discipline, responsibility, patience, spiritual calm, peer support, and awareness of worship. Conceptually, this study contributes a habituation-tadabbur character formation model, while technically it offers a school-based religious culture strategy through planning, teacher modeling, monitoring, and reflective Qur’anic learning.